Determining who has custody of children after divorce in Vietnam: A legal perspective from children’s rights - Nguyen Thi My, Linh (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2025)
The right of parents to custody of children after divorce is a significant privilege and obligation under marriage law, which is of interest to the legal systems of many countries, including Vietnam. The provisions regarding the right of parents to directly nurture their children post-divorce impose a responsibility on parents and contribute to the protection of children's rights. Competent state agencies and organisations are also responsible for protecting children when parents divorce and the family unit is no longer intact. Consequently, the rights and interests of children are guaranteed to be upheld in the event of a divorce. Furthermore, the implementation of parental rights and responsibilities after divorce helps children avoid psychological complexes and trauma, thereby ensuring their optimal development in all domains. However, the right to custody of children by parents after divorce is not inherent in all divorce cases. This right is reserved for minors and adult children who have lost civil capacity, are unable to work, and have no assets to support themselves. To meet the objective requirements of societal and familial development, the current Vietnamese law on marriage and family, in general, and the law on protecting children's rights when parents divorce, in particular, have been developed. Nevertheless, the Vietnamese law on marriage and family still has disadvantages and inadequacies, which, in practical cases, create challenges in implementing the right to sole custody of children when parents divorce, alongside its positive aspects. This article examines the legal issues related to the right to custody of children in the event of divorce under Vietnamese law. It also suggests strategies for enhancing the law using the legislative experiences of various jurisdicions countries worldwide.